TAX RELATIONS AND COMPETENCE DIALECTIC BASIS OF DEVELOPMENT - Ashurova Oltin Yuldashevna; To'lqinova Mushtariy; Yu'ldosheva Aziza (Ecominds Press, 2025)
This article discusses the theoretical and practical nature of tax capacity and its role in economic development. The content and nature of tax capacity, their interdependence and connections in the system of market relations are highlighted. The article explains the development of tax relations, their modification and the formation of new types of taxes with their impact on economic processes.
Keywords: Tax capacity, tax system, tax relations, economic development, budget stability, market relations, tax revenues, socio-economic development, tax modification, tax theory.